1928
DOI: 10.1002/cber.19280610502
|View full text |Cite
|
Sign up to set email alerts
|

Zur Methode der Hydrierung mit Natrium‐amalgam

Abstract: Abteilung B (Abhandlungen) -9. Mai. R i c h a r d W i l l s t a t t e r , Franz S e i t z und E r w i n B u m m :Zur Methode der Hydrierung mit Natrium-amalgam. (Eingegangen am 21. Marz 1928.) I. T h e o r i e d e r Amalgam-Wirkung.Die Hydrierung durch Natrium-amalgam wurde von A. K e k u l e l ) , H. Kolbe2), A. v o n Baeyer3) und anderen Forschern so erklart, daB das Amalgam durch Wasser zersetzt werde, und daB sich der nascierende Wasserstoff an reaktionsfahige Atomgruppen organischer Verbindungen anlagere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1932
1932
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Until recent years the theory of 'nascent' hydrogen was widely accepted, and is still used by many authors. Willstátter and his coworkers (328) have, however, rejected this 'naseent'-hydrogen mechanism, as the result of a careful study of the course of reductions by sodium amalgam. They showed that it was possible to obtain yields of reduced product as high as 90 per cent (based on sodium), and considered that this would be impossible if hydrogen atoms were the actual reducing agent.…”
Section: B Theories Of Chemical Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recent years the theory of 'nascent' hydrogen was widely accepted, and is still used by many authors. Willstátter and his coworkers (328) have, however, rejected this 'naseent'-hydrogen mechanism, as the result of a careful study of the course of reductions by sodium amalgam. They showed that it was possible to obtain yields of reduced product as high as 90 per cent (based on sodium), and considered that this would be impossible if hydrogen atoms were the actual reducing agent.…”
Section: B Theories Of Chemical Reductionmentioning
confidence: 99%
“…Addition of lithium takes place with increasing ease in the order: naphthalene, phenanthrene, anthracene (265). Aromatic compounds are not usually attacked by sodium amalgam or aluminum amalgam (291), although anthracene is reduced by both (143, 291) and terephthalic acid is reduced by sodium amalgam (328). The addition of hydrogen or metals to polynuclear hydrocarbons has a strong tendency to occur in the 1,4-positions, and in this respect these compounds resemble the 1,4-diaryIbutadienes.…”
Section: G Reduction Of Aromatic Hydrocarbonsmentioning
confidence: 99%
“…The products are benzene, diphenylamine, triphenylamine, and a little aniline (197). The formation of diphenylamine, for instance, might conceivably be represented by equations 202 to 206, 2 CeHsCl + 4 Na -> 2 NaCl + 2 C,H6Na (202) 2 C,H5Na + 2 NHS -» 2 C6H6 + 2 NaNH2 (203) C6H6C1 + NaNH2 -> C6H5NH2 + NaCl (204) CsHeNH2 + NaNH2 -> NH3 + C6H5NHNa (205) C8H6NHNa + C6H6C1 -> (C6H6)2NH + NaCl (206) but it has been found that reactions of the type expressed in equation 206 do not occur in liquid ammonia under such conditions (199,51).…”
Section: The Mechanism Of the Wurtz-fittig Reactionmentioning
confidence: 99%
“…A striking contrast to this behavior is presented by catalytic hydrogenation of the same substances, which yields no intermediate unsaturated products and proceeds more readily with the "olefinic" compounds than with the benzene derivatives. Willstatter and his coworkers (202) have made a quantitative investigation by carrying out the reduction process in an inert atmosphere, calculating the total amount of nascent hydrogen formed from the titre of the alkaline aqueous solution, and determining the evolved hydrogen gas as water after oxidation. They soon learned that even the nature of the reduction products, as well as the activity of the amalgam, was dependent on its purity.…”
Section: The Mechanism Of the Wurtz-fittig Reactionmentioning
confidence: 99%
“…Οι πρώτες σε βάθος παρατηρήσεις έγιναν από τον SciilenR μερικά χρόνια αργότερα [9][10][11] . Ο Willstaetter φαντάσθηκε ότι το μέταλλο (Na ή Κ) ήταν ενωμένο στο δακτύλιο 12 . 19 .…”
Section: πιβακας ιunclassified